A modified bone lid for osteoplastic surgery of the maxillary sinus. Issue 7 (July 2015) - Katauczek, F.; Nkenke, E.; Wagner, F.; Seemann, R.
Abstract Major problems associated with the use of a bone lid for osteoplastic surgery of the maxillary sinus, as first described by Lindorf, are the possibility of postoperative dislocation of the bony fragment into the sinus (floating bone), as well as inflammatory resorption or fracture of the very thin removed trap door fragment. We describe a technique that prevents dislocation of the bone lid and allows for very good visualization of the entire sinus by a simple extended design and the use of resorbable pins. With the use of this extended bone lid, the removal of severely dislocated teeth, implants, sinus pathologies, or foreign bodies can be performed easily. Furthermore, this is an advantageous approach for large orbital fractures, especially those of the posterior half.